INVESTIGATION OF SEVERE PROGNOSTIC FACTORS IN PATIENTS WITH DEEP NECK INFECTIONS AT CHO RAY HOSPITAL - Ngo, Van Cong; Vo, Nguyen Thuy Uyen (Tạp chí Tai Mũi Họng Việt Nam, 2024)
Background: Deep neck infection (DNI) is a severe otorhinolaryngological emergency with a high risk of rapid spread to critical structures, leading to complications and high mortality rates.Objective: This study aims to identify severe prognostic factors in patients with DNI at Cho Ray Hospital (2023–2024).Methods: A cross-sectional study was conducted with multivariate regression analysis to identify factors associated with severe progression and mortality. Data were collected from 151 patients medical records.Results: Prognostic factors for ICU admission included dyspnea, NLR ≥20, necrotizing fasciitis, pneumonia, and mediastinitis. Prognostic factors for mortality included dyspnea, chest pain, NLR ≥20, necrotizing fasciitis, and septic shock.Conclusion: Identifying severe prognostic factors can help clinicians recognize high-risk patients early for timely intervention, reducing complications and mortality.